2014
DOI: 10.1007/s11095-013-1260-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Increases in Danazol Exposure with Dose in Older vs. Younger Beagle Dogs: The Potential Role of Differences in Bile Salt Concentration, Thermodynamic Activity, and Formulation Digestion

Abstract: Differences in animal cohort can have a significant impact on drug absorption from lipid based formulation. For danazol, bioavailability was enhanced under some circumstances in older animals. In vitro experiments suggest that this was unlikely to reflect changes to metabolism or lipolysis, but might be explained by increases in luminal bile salt/phospholipid concentrations in older animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
3
6
1
Order By: Relevance
“…The polymers E 100, HPMCAS:HF, and HPMC E4M were therefore employed in initial experiments to determine whether drug loading significantly affected PPI performance. The in vitro concentration profiles of fenofibrate after dispersion and digestion of the three formulations (Type IIIA-MC, IIIB-MC, and IV) at high drug load (85% saturation), resulted in more precipitation than those obtained at low (40% saturation) drug load, in agreement with previous studies using fenofibrate 38,39,43,68 and other PWSDs 17,53,69 in LBFs. This can be attributed to the higher AP MAX reached at higher drug load, which increases the maximum supersaturation ratio (S M ) and therefore the pressure applied on the formulation to maintain supersaturation without drug precipitation.…”
Section: Molecular Pharmaceuticssupporting
confidence: 89%
“…The polymers E 100, HPMCAS:HF, and HPMC E4M were therefore employed in initial experiments to determine whether drug loading significantly affected PPI performance. The in vitro concentration profiles of fenofibrate after dispersion and digestion of the three formulations (Type IIIA-MC, IIIB-MC, and IV) at high drug load (85% saturation), resulted in more precipitation than those obtained at low (40% saturation) drug load, in agreement with previous studies using fenofibrate 38,39,43,68 and other PWSDs 17,53,69 in LBFs. This can be attributed to the higher AP MAX reached at higher drug load, which increases the maximum supersaturation ratio (S M ) and therefore the pressure applied on the formulation to maintain supersaturation without drug precipitation.…”
Section: Molecular Pharmaceuticssupporting
confidence: 89%
“…19 This was suggested to reflect either saturation of first pass metabolism or an increase in thermodynamic activity at higher doses. Interestingly, the dose-dependent increase in bioavailability was evident in only one cohort of (older) animals, and not in another (younger) group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies of danazol absorption from SEDDS revealed nonlinear increases in exposure (bioavailability) with increasing drug dose in dogs. 19 This was suggested to reflect either saturation of first pass metabolism or an increase in thermodynamic activity at higher doses. Interestingly, the dose-dependent increase in bioavailability was evident in only one cohort of (older) animals, and not in another (younger) group.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations